Study on drying performance of high voltage cable buffer layer material - Zhang Jing; Liu Jinghua; Luo Chuanxian; He Liang; Cheng Lifeng; Cai Yuru (MATEC Web of Conferences, 2022)
In order to study the failure mechanism of high-voltage cable buffer layer caused by moisture and the performance of the material after immersion and drying, according to the structure and size of 110 kV XLPE cable, the requirements for the separation distance between corrugated aluminum sheath and insulating outer shield before and after the change of buffer layer resistivity caused by moisture were calculated, the influence of moisture on ablation failure was analyzed. The test platform of buffer layer material was built, the properties of two kinds of materials without water immersion and after water immersion drying were tested, including semi-conductive buffer water-blocking tape and semi-conductive buffer tape. The results show that when the moisture content was large, the resistivity of the buffer layer increases, which reduces the requirements of the allowable separation distance of the cable, and was more likely to cause the discharge and ablation of the buffer layer. The water in the buffer layer was removed by drying at 70 °C, with thickness, weight, the water content, elongation at break, breaking strength and volume resistivity can be recovered, which verifies that the heating drying method is feasible for the removal of water from the buffer layer.